Pipeline corrosion and cathodic protection a practical manual for corrosion engineers, technicians, and field personnel - Parker, Marshall E. (Elsevier, 1999)
This update of Marshall Parker's classic text contains the latest "hands-on" information for taking measurements and making the calculations necessary for cathodic protection of buried pipe lines. Essentially a practical field manual for corrosion technicians and engineers, it is a simple and direct introduction to the fundamentals of a complex subject. The contents cover soil resistivity surveys, potential surveys, line currents, current requirement surveys, rectifier systems for coated lines, ground bed design and installation, galvanic anodes on coated lines, hot spot protection, bond protection, stray current electrolysis, interference, operation and maintenance, and coating inspection and testing. There are also helpful appendixes that explain the fundamentals of underground corrosion, basic principles of cathodic protection, tables of properties of metals, and attenuation equations. While other books on corrosion are sometimes too theoretical for practical work, Pipe Line Corrosion and Cathodic Protection, Third Edition, shows you how to take actual field measurements and apply them to design a well-protected system.